2013
DOI: 10.1179/2047773213y.0000000114
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus detection by real-time PCR and pp65-antigen test in hematopoietic stem cell transplant recipients: a challenge in low and middle-income countries

Abstract: Aim: Cytomegalovirus (CMV) infection is one of the most common complications in patients submitted to hematopoietic stem cell transplant (HSCT). Pre-emptive therapy has been indicated in patients with laboratory evidence of CMV replication. The aims of this study were to compare real-time PCR or pp65 antigen assay methodologies to detect CMV replication in HSCT patients, define a viral load threshold for initiation of pre-emptive therapy, and assess the feasibility of its implementation in hospitals of countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…In spite of the low rate of HCMV‐disease outcome in this study, it was observed a tendency on clinically relevant HCMV viremia and positive pp65 antigenemia test ( P = .053). As a semi‐quantitative method, pp65 antigenemia test has a high predictive value for active infection and progression to disease, which is consistent with higher viral loads . Furthermore, patients with clinically relevant HCMV viremia presented a significant association with acute rejection, which corroborates with the findings of a larger multicentric study .…”
Section: Discussionsupporting
confidence: 83%
“…In spite of the low rate of HCMV‐disease outcome in this study, it was observed a tendency on clinically relevant HCMV viremia and positive pp65 antigenemia test ( P = .053). As a semi‐quantitative method, pp65 antigenemia test has a high predictive value for active infection and progression to disease, which is consistent with higher viral loads . Furthermore, patients with clinically relevant HCMV viremia presented a significant association with acute rejection, which corroborates with the findings of a larger multicentric study .…”
Section: Discussionsupporting
confidence: 83%
“…The intracellular B cell-specific transcription factor BOB1 is abundantly presented in B cell malignancies including acute lymphoblastic leukemia, chronic lymphocytic leukemia and mantle-cell lymphoma but also in multiple myeloma [ 19 , 39 42 ]. The pp65 protein of CMV (cytomegalovirus capsid derived antigen) is a major target of immune responses in CMV infections [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Presently, most methods mention the relative sensitivity (%) of detection for CMV antibodies [ 8 , 36 ], but little in provided about absolute sensitivity. Compared other methods, the absolute sensitivity of BIE can reach 0.01 IU/mL, and it has good resolution in the range of 0.1–1.0 IU/mL on the calibration curve for quantitative detection.…”
Section: Discussionmentioning
confidence: 99%